Karakterisasi Morfologi, Anatomi, dan Fisiologi Tujuh Klon Unggul Kopi Robusta - Sakiroh Sakiroh; Meynarti Sari Dewi Ibrahim (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Morphological characterization of superior Robusta coffee plants has been widely studied, but for the anatomical and physiological character is still relatively limited. Result of this characterization is important as a basic information in order to create the new superior varieties. The purpose of this study was to investigate the morphological, anatomical, and physiological characteristics of seven clones of Robusta coffee (SA 203, BP 534, BP 42, BP 409, BP 939, BP 308 and BP 436). The experiment was conducted at Pakuwon Experimental Station and Integrated Laboratory of Indonesian Industrial and Beverage Crops Research Institute, Sukabumi, West Java, from October to November 2019. The Completely Randomized Design with 7 Robusta coffee clones as treatments and three replications was used in this study. The variable observed were morphological (leaf area), anatomical (stomata shape and density) and physiological characters (chlorophyll a, chlorophyll b and total chlorophyll). The results showed that the leaf area of the first and third leaves of seven clones of Robusta coffee were relatively uniform. The stomata shape of Robusta coffee leaf is parasitic type (Rubiaceous) type. The SA 203 and BP 409 clones have the fewest stomata contents. The content of chlorophyll a, b, and total in the first and third leaves varies between clones. Chlorophyll content in the basal, middle, and apical leaf were relatively uniform, except clones SA 203 and BP 939 for the first leaf, and SA 203 and BP 436 for third leaf. The correlation analysis showed a positive relationship between leaf area and chlorophyll content.